Development of Roasted Coconut Production Method using Hot Air with Drying Cyclone - Puzu, Ni-oh; Piya, Ibroheng; Palasai, Wasan; Sa-nor, Sabree (Princess of Naradhiwas University Journal, 2020)
This research proposed the production development of roasted coconut process using hot air together with cyclone as a continuous production process instead of the conventional production method, which roasted by hot pan. The experiment was conducted from designing and fabricating process system, which employed centrifugal blower to generate air flow and electric heaters as a heat source. Continuous feeding rate of fresh coconut was maintained at 200 g/min and 15 rounds. Air temperatures at 70, 80, and 90 ºC and air velocities at 25.7, 32.0, and 38.0 m/s were investigated. The results found that increasing air temperature had more influence on decreasing the rounds feeding than that increasing air velocity factor. For temperature at 90 ºC and velocity at 38.0 m/s, drying rate was the highest. This showed that the moisture content was lower than 0.66%db after finishing the 8th round of feeding before becoming constant moisture state. The results can be developed the method which employed hot air and cyclone for roasting coconut as continuous production instead the convention method.